Transactional sex amongst young people in rural northern Tanzania: an ethnography of young women's motivations and negotiation - Wamoyi, Joyce (BioMed Central, 2010)
BACKGROUND: Material exchange for sex (transactional sex) may be important to sexual relationships and health in certain cultures, yet the motivations for transactional sex, its scale and consequences are still little understood. The aim of this paper is to examine young women's motivations to exchange sex for gifts or money, the way in which they negotiate transactional sex throughout their relationships, and the implications of these negotiations for the HIV epidemic. METHOD: An ethnographic research design was used, with information collected primarily using participant observation and in-depth interviews in a rural community in North Western Tanzania. The qualitative approach was complemented by an innovative assisted self-completion questionnaire. FINDINGS: Transactional sex underlay most non-marital relationships and was not, per se, perceived as immoral. However, women's motivations varied, for instance: escaping intense poverty, seeking beauty products or accumulating business capital. There was also strong pressure from peers to engage in transactional sex, in particular to consume like others and avoid ridicule for inadequate remuneration. Macro-level factors shaping transactional sex (e.g. economic, kinship and normative factors) overwhelmingly benefited men, but at a micro-level there were different dimensions of power, stemming from individual attributes and immediate circumstances, some of which benefited women. Young women actively used their sexuality as an economic resource, often entering into relationships primarily for economic gain. CONCLUSION: Transactional sex is likely to increase the risk of HIV by providing a dynamic for partner change, making more affluent, higher risk men more desirable, and creating further barriers to condom use. Behavioural interventions should directly address how embedded transactional sex is in sexual culture.